New BN/SiOC aerogel composites fabricated by the sol-gel method with excellent thermal insulation performance at high temperature. (5th January 2020) - Yang, Haixia; Li, Chunming; Yue, Xiandong; Huo, Jianchun; Ye, Feng; Liu, Jingxiao; Shi, Fei; Ma, Jie
Abstract: Although pure silicon oxycarbide (SiOC) aerogels have unique properties of low density and high temperature resistance, they are still difficult to apply at a large scale due to brittleness. To overcome this drawback, a strong boron nitride/silicon oxycarbide (BN/SiOC) aerogel composite with high-temperature resistance and thermal insulation was prepared by the sol-gel method and pyrolysis of the precursor aerogel. The microstructural, mechanical and thermal insulation properties of the composites were investigated, and the effect of the BN content on the microstructure and properties was also clarified. The results indicate that the obtained mesoporous composites exhibit low thermal conductivity (0.04–0.20 Wm −1 K −1 ) and high-temperature resistance (∼1300 °C). As the BN content increased from 0 to 15 vol %, the compressive strength of the composites increased from 2.2 to 20.3 MPa. The obtained composites exhibit considerable promise in high-temperature thermal insulation applications. Graphical abstract: Image 1 Highlights: The sol-gel method was developed for preparing BN/SiOC aerogel composites. The mechanical properties of the composites were considerably improved by adding BN particles. The BN/SiOC aerogel composites possess nanometre pore structures. The composites have excellent thermal insulation performance at high temperature.